La contribution de l'Espagne au développement de la typographie Grecque (Minerva. Revista de Filología Clásica, 2019)
In the frame of the Greek culture of the Spanish Renaissance the author focuses his attention specially on the Greek type cast by Guillén de Brocar in Alcalá for the Complutensian Polyglott, a very important contribution to the Greek typography.